2021
DOI: 10.11591/edulearn.v15i2.19863
|View full text |Cite
|
Sign up to set email alerts
|

Learning adaptation during the COVID-19 pandemic in Muhammadiyah inclusion schools

Abstract: The Muhammadiyah organization has inclusive schools that need to adapt during the coronavirus disease 2019 (COVID-19) pandemic. This study aimed to analyze the adaptation strategies carried out by two Muhammadiyah inclusion schools in Surabaya, Indonesia, Sekolah Peduli Anak Hebat (SPAH) and the Sekolah Kreatif Surabaya. This study used a qualitative descriptive approach with a phenomenology method to see the particular context of the two inclusion schools' learning situation during the COVID-19 pandemic. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 18 publications
0
14
0
2
Order By: Relevance
“…Meanwhile, the results of other studies reveal that delays in work assignments occur due to poor student motivation and no desire to accept challenges during the COVID-19 pandemic [16]. Anxiety, confusion related to learning are also factors for students to delay doing the assignments given [25], [26] shows that the strategy for adapting online learning during the COVID-19 pandemic must have cooperation with related parties, namely parents, educators, and students. The procrastination experienced by students causes a decrease in student academic achievement [27].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the results of other studies reveal that delays in work assignments occur due to poor student motivation and no desire to accept challenges during the COVID-19 pandemic [16]. Anxiety, confusion related to learning are also factors for students to delay doing the assignments given [25], [26] shows that the strategy for adapting online learning during the COVID-19 pandemic must have cooperation with related parties, namely parents, educators, and students. The procrastination experienced by students causes a decrease in student academic achievement [27].…”
Section: Discussionmentioning
confidence: 99%
“…They found that the Participatory Action Research conducted by the Muhammadiyah residents in this area is a practical step and an excellent example of suitable structural and cultural approaches that various entities can use to mitigate the potential for social assistance corruption during the pandemic. Meanwhile, Lestari, Hamsia and Setiyawan ( 2021 ) analysed the adaptation strategies employed by two Muhammadiyah inclusion schools in Surabaya, Indonesia, namely Sekolah Peduli Anak Hebat (SPAH) and Sekolah Kreatif Surabaya, in the education sphere. The study discovered that these strategies could help coordinate parents, teachers and students, build community cooperation, and make flexible and accessible learning policies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…STEAM learning can encourage students to explore existing abilities, in their own way and also lead to different and unexpected works from each individual or group. In addition, the ability to collaborate, cooperate and communicate can be raised in the learning process because this approach is carried out in groups (Lestari et al, 2021;Quigley et al, 2017;Bahrum et al, 2017). STEAM learning is also used as an approach in teaching physics to students.…”
Section: Introductionmentioning
confidence: 99%